Post-disaster food safety and food security: An example of the Türkiye earthquake - Cakir, Muhammet Ali; Mercan, Yeliz; Icyer, Necattin Cihat; Bozkurt, Fatih (SPRINGER, 2025)
The present study aimed to determine the risk levels affecting food safety and security in foods distributed to earthquake victims by organizations. This descriptive and cross-sectional study was conducted in food distribution organizations in Kahramanmara & scedil; and Hatay between 20-24 February 2023 (N = 40). The data were collected face-to-face by using the Descriptive Data Form and Food Safety and Security Observation Form (FSSOF) developed by the researchers. According to FSSOF, organizations had a 41.6% risk concerning food safety and security. According to the multiple linear regression analysis, organizations that did not control the foods were found to be associated with an increased total score of FSSOF (beta: -0.527, p = 0.010). No relationships could be found between the type of organization, the population served, having a food technologist and/or dietitian, the distance between the organization and waste, and the total scores of FSSOF (p > 0.05). The organizations that did not control the food were found to be associated with Organization-specific conditions (beta: -0.623, p = 0.002), Food distribution conditions (beta: -0.531, p = 0.015), Personnel hygiene (beta: -0.608, p = 0.005), Food security (beta: -0.480, p = 0.036) and Environmental conditions (beta: -0.537, p = 0.018) were found to be associated with an increased level of risks. Also, not having an engineer and/or dietitian was associated with an increased risk of Food storage practices (beta: -0.469, p = 0.005), and increased the number of staff was associated with an increased risk of Organization-specific conditions (beta: 0.348, p = 0.007). The level of risk of the organizations concerning food safety and security was found to be relatively high. Control of the food provided was the most important determinant of food safety and security.
Keywords: Earthquake; Food control; Food distribution; Food safety; Food security; Natural disaster; Risk; DISASTER; KNOWLEDGE; ATTITUDES; HANDLERS; Food Science & Technology